Reduced Dielectric Losses for Underground Cable Distribution Systems - Hamzah Eteruddin (International Journal of Applied Power Engineering (IJAPE), 2012)
This paper describes the process to reduce dielectric losses for underground cable distribution system. As already known, that system is an alternative solution to energy distribution systems in urban areas. Influence of large capacitance is a separate issue that needs to be resolved. Large capacitance effect on Express Feeder of 10 miles long has resulted in power losses more than 100 MW per month. In the no-load condition, current dispatch has recorded 10 Amperes, and has increased the voltage at receiving end by 200-500 Volts, with leading power factors. Installation of the inductor to reduce cable loss dielectrics is done by changing the power factor (pf) to 0.85 lagging. After installation of the inductor, which is 5 mH/700 kVAR, dielectric losses is reduced to 3.57%, which is from 105,983 kW to 102,195 kWh per month. The capacitive leakage current has also been reduced from 249.61 Ampere to 245.17 Ampere.